2003
DOI: 10.1002/cjce.5450810374
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Injection of Gas‐Liquid Jets into Fluidized Beds of Fine Particles

Abstract: montrent un bon accord avec les données expérimen-tales. Le présent modèle peut servir à caractériser le comportement de jets gaz-liquide (vaporisations fines) injectés dans des lits fluidisés de particules fines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…A weaker triboelectric signal was expected to be observed in this region, since the solids have not yet been fully accelerated by the jet. However, the observed length of the low-signal region ranged between 30 and 50 nozzle diameters, compared to the calculated length of up to 2.1 nozzle diameters for the potential core by Ariyapadi et al [1]. Clearly, the observed region of weak signal does not represent just the potential core region as it is much too long.…”
Section: Triboelectric Studymentioning
confidence: 72%
See 2 more Smart Citations
“…A weaker triboelectric signal was expected to be observed in this region, since the solids have not yet been fully accelerated by the jet. However, the observed length of the low-signal region ranged between 30 and 50 nozzle diameters, compared to the calculated length of up to 2.1 nozzle diameters for the potential core by Ariyapadi et al [1]. Clearly, the observed region of weak signal does not represent just the potential core region as it is much too long.…”
Section: Triboelectric Studymentioning
confidence: 72%
“…8. The initial low signal region was initially attributed to the existence of the potential core region described by De Michele et al [21] and Ariyapadi et al [1]. A weaker triboelectric signal was expected to be observed in this region, since the solids have not yet been fully accelerated by the jet.…”
Section: Triboelectric Studymentioning
confidence: 94%
See 1 more Smart Citation
“…[45][46][47] Li et al [6] found that the empirical correlations listed in Table 1 are unable to accurately predict the penetration of supersonic jets in high temperature fluidised beds. The Froude number has been used in the empirical correlations of Merry, [37] Benjelloun [39] and Ariyapadi et al [48] Li et al [6] proposed a new empirical correlation based on experimental data collected from supersonic nozzles discharging into hot fluidised beds: Figures 17 and 18 show that correlations from both Merry and Yates overestimated the jet penetration length.…”
Section: Correlation To Predict the Jet Penetrationmentioning
confidence: 99%
“…Investigations with nonvaporizing horizontal gas-liquid spray jets have shown that, with a proper design of the injection nozzle, it is possible to penetrate over several decimeters into the bed before the jet breaks up [91,92]. Investigations with nonvaporizing horizontal gas-liquid spray jets have shown that, with a proper design of the injection nozzle, it is possible to penetrate over several decimeters into the bed before the jet breaks up [91,92].…”
Section: Injection Of Liquid Reactants Into Fluidized Bedsmentioning
confidence: 99%